Africa and IMF conditionality the unevenness of compliance, 1983-2000 - Akonor, Kwame (New York Routledge, 2006)
Ghana was one of the first African countries to adopt a comprehensive IMF reform program and the one that has sustained adjustment longest. Yet, questions of Ghana's compliance - to what extent did it comply, how did it manage compliance, what patterns of non-compliance existed, and why? - have not been systematically investigated and remain poorly understood.
Includes bibliographical references (p. 137-154) and index.
Keywords: International Monetary Fund--Ghana.